Effects of Prescribed Fire Timing on Stocker Cattle Performance, Native Plant Composition, Forage Biomass, and Root Carbohydrate Reserves in the Kansas Flint Hills: Year One of Six - Z. M. Duncan; A. J. Tajchman; M. P. Ramirez; J. Lemmon; W. R. Hollenbeck; D. A. Blasi; K. C. Olson (Kansas Agricultural Experiment Station Research Reports, 2020)
Objective:Our objective was to document the effects of prescribed fire timing on yearling beef cattle performance, native plant composition, and forage biomass accumulation in the Kansas Flint Hills. Study Description:Our study took place at the Kansas State Beef Stocker Unit located northwest of Manhattan, KS. Pastures were assigned to one of three prescribed burn treatments: early spring (April), mid-summer (August), or early fall (October). Treatments were applied and yearling heifers (n = 360) were subsequently grazed from May to August. Native plant composition and forage biomass were evaluated annually in late June and early July. The Bottom Line:The first year of data from a six-year study indicated that prescribed fire timing affected stocker cattle performance and forage biomass availability but not basal cover of forage grasses and forbs.
Keywords: stocker cattle; prescribed fire; grazing